Creating effective sales and marketing relationships - Le Meunier-FitzHugh, Kenneth; Le Meunier-FitzHugh, Leslie Caroline (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
The aim of this book is to discuss how corporate sales and marketing functions can operate collaboratively. Although effective sales and marketing interactions are critical to achieving organizational goals, their practical working relationship is frequently described as being unsatisfactory. Sales and marketing have developing their own perceptions of what should be achieved and how it can be realized. Because of the differences that exist between sales and marketing, the exploration of the issues and possible solutions to the sales and marketing dilemma offers an exciting opportunity for practitioners and academics, both in the context of management, and training and development programs, to deliver superior customer value. We will explore how sales and marketing can become more competitive in the face of dynamic and borderless markets, where lead generation is less important than building long-term relationships with customers. The book considers the follow areas related to the sales and marketing interface: How the crises in the sales and marketing interface became established. How alignment between sales and marketing can be achieved in lead generation. Consideration of the formal and informal methods of communication that can assist in establishing inter-functional collaboration. How collaboration between sales and marketing can improve customer relationships. The role of senior management in improving sales and marketing working relationships, and the optimization of the sales and marketing interface.
1. The sales and marketing interface -- Creating customer value -- Operation of the sales and marketing interface -- Collaboration verses integration -- The changing role of sales -- The changing role of marketing -- 2. Crises in working relationships between sales and marketing -- Growth or conflict -- Barriers to collaboration -- Organizational barriers -- Location barriers -- Inconsistent processes -- Competing for resources and budgets -- Informational constraints -- Outcomes of conflict between sales and marketing -- 3. Alignment and effective working relationships in lead generation -- Aligning sales and marketing -- Process alignment -- Lead generation and the sales funnel -- Consultative selling -- Effects of e-marketing -- Selling direct through the web -- How should sales and marketing work together? -- 4. How should sales and marketing -- What is communication? -- Building market information systems -- Joint planning -- Communicating with the customer -- New product development -- 5. The role of sales and marketing in customer relationships -- Customer focus and relationship building -- Trust between buyers and sellers -- Value co-creation -- 6. Managing the sales and marketing interface -- Motivating collaboration -- Integration mechanisms -- Cross-functional meetings and joint planning -- Cross-functional teams -- Cross-functional training -- Job rotation -- Rewards alignment -- 7. Optimizing the sales and marketing interface -- Structure and process -- The role of learning in collaborative behavior -- Customer value -- Practical integration -- Management role -- Five key points in the sales and marketing collaboration -- References -- Index.
Includes bibliographical references (pages 87-95) and index.
Title from PDF title page (viewed on January 26, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Sales management; Marketing -- Management; Sales; Marketing; Conflict; Collaboration; Management; Communication; Lead Generation; Resources; Value Creation; Competitive Advantage; Electronic books